Ludwigs Angina: a study of 50 cases (Bangladesh Journal of Otorhinolaryngology, 2009)
Objective: To evaluate the clinical outcome, morbidity and mortality of patients diagnosed as Ludwig's angina. Study design: Retrospective study. Setting: Department of Otolaryngology & Head and Neck Surgery, Dhaka Medical College Hospital and Apollo Hospitals Dhaka. Patients and Methods: 50 patients were included in this study (36 males and 14 female) between the ages of 8 and 78 years (mean, 45.5 years) who were treated between January 2007 and December 2008 in the department of Otolaryngology and Head-Neck surgery, Dhaka Medical College Hospital and Apollo Hospitals Dhaka. Etiology, microbiology, associated systemic diseases, treatment, airway management, duration of hospital stay and outcome were reviewed. Results: Most common age group was 3rd decade (42%) and 72% patients were male. Most patients came from poor socio-economic condition and rural area of Bangladesh. 100% patients presented with neck swelling, pain, tenderness and fever. Dental infection was documented as the most common cause (70%) of Ludwig's angina, followed by infection of the tonsils (10%) and submandibular gland (6%). Systemic illnesses included diabetes mellitus (30%) and chronic renal failure (4%).Streptococcus is commonest organism found in culture of pus. Intravenous antibiotics were started immediately in all patients. 4 patients underwent emergency tracheostomy. 40 patients underwent incision and drainage. Infected tooth/ teeth were also removed at the same time. Postoperatively, the airway was secured by endotracheal intubation in 1 case and by tracheotomy in 5 cases. In 88 %( 44 patients) of the cases, no artificial airway was used. 9 patients were managed in the intensive care unit for 1 to 3 days. All except 1 patient made uneventful recoveries and they were discharged after 3 to 26 days of hospitalization (mean, 14.1 days). Conclusion: Airway protection, aggressive antibiotic therapy and surgical decompression can significantly alter the mortality rate of Ludwig's angina. Key Words: Cellulitis, Ludwig's angina, surgical decompressionDOI: 10.3329/bjo.v14i2.3281 Bangladesh J of Otorhinolaryngology 2008; 14(2) : 51-56